Ketidakadilan Gender pada Tokoh Perempuan dalam Novel Terusir Karya Buya Hamka: Kajian Kritik Sastra Feminis - Mukhibun, Akhmad; Wardani, Nugraheni Eko (GERAM: Gerakan Aktif Menulis, 2023)
Gender inequality often occurs in women. This is because the construction of a patriarchal society places women in the domestic sphere so that women are seen as helpless, weak, and in a lower position than men. This research aims to describe and explain the forms of gender injustice experienced by female characters in the Novel Terusir by Buya Hamka. This research is qualitative research using a feminist literary criticism approach. The data source is a document from the Novel Terusir by Buya Hamka. The sampling technique used was purposive sampling, namely sampling with the aim of considering the content of gender injustice towards female figures. Data collection techniques use document analysis. Data analysis uses flowing model analysis. Data validity testing was carried out by theoretical triangulation and inter-researcher triangulation. The results of the research showed that 59 data were found on gender inequality in female figures, namely 14 data on marginalization, 4 data on subordination, 20 data on stereotypes, 20 data on violence, and 1 data on workload. The most dominant form of gender injustice is stereotypes and violence against female characters. This happened because Mariah was a lonely woman and did not come from a wealthy family. It is hoped that the results of this research will be useful for enriching literary studies, especially the study of feminist literary criticism